Developed Jepara 3D Augmented Reality Furniture Catalog Application Based on Android - Musthofa, Muhammad Naufal Alfa'iz; Handayani, Irma (International Journal Software Engineering and Computer Science (IJSECS), 2023)
Jepara, a regency in Central Java, Indonesia, stands as a prominent hub for the wooden furniture industry, boasting a reputation that extends globally. Traditional marketing approaches, particularly the use of physical catalogs, encounter notable challenges in this digital era. This study identifies the limitations of conventional print catalogs in generating consumer interest and facilitating access to store information in Jepara’s teak furniture market. To address these challenges, we introduce an innovative solution employing Augmented Reality (AR) technology. Utilizing the waterfall development methodology, this research develops an AR application compatible with Android devices. This application transforms the furniture shopping experience by presenting 3D visualizations of products, complete with detailed dimensions, thus enabling consumers to gauge the actual size of the items. Furthermore, the application curates a list of high-rated furniture stores in Jepara, offering comprehensive store information. This integration of AR technology not only enriches the consumer experience but also adds an interactive dimension to the furniture purchasing process